Mediated by job satisfaction (Empirical Study: Employees of Perum Indonesian Aviation Navigation Service Provider Jakarta Air Traffic Services Center Branch) - Lestari Wulandari Annisia Hadi; Andreas Heryjanto (Asian Journal of Social and Humanities, 2023)
The purpose of this study is to determine the influence of the work environment and leadership style on employee loyalty with job satisfaction as a mediating variable in Perum LPPNPI JATSC Branch Office. This study used a quantitative approach. The survey was conducted to 180 respondents with the criteria that respondents were employees of Perum LPPNPI JATSC Branch Office. Data was analyzed with Structural Equation Model (SEM) and data processing using Partial Least Square (PLS) approach with SmartPLS program version 4.0. The results showed that the variables of work environment, leadership style and job satisfaction had a positive and significant influence on employee loyalty. In addition, the work environment and leadership style also have a positive and significant influence on job satisfaction. The results of indirect influence testing show that the job satisfaction variable mediates the relationship between the work environment and employee loyalty and also mediates the relationship of leadership style to employee loyalty. This research provides practical implications for companies to always pay attention to the work environment and leadership style used by their leaders so that employees can work safely and comfortably so that employee loyalty and job satisfaction can increase